PENDIDIKAN (AGAMA) ISLAM DI PERGURUAN TINGGI: TAWARAN DIMENSI ESOTERIK AGAMA UNTUK PENGUATAN SDM - Sulaiman, Rusydi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2015)
IslamicEducation in University Level: An Offer of Religious Esoteric Dimension for Strengthening HumanResource. The term of PI (Pendidikan Islam) and PAI (Pendidikan Agama Islam) have been being discussedamong lectures. Which one is more general than other? Conceptually, both terms are not too fixed. Hence, itshould be clear the meaning then to be one paragdigm. In fact, some alumna of Tarbiyah Faculty who took thisprogram are doubtful how to strengthen the concept of PAI (Pendidikan Agama Islam). This article is attemptedto answer and make a concept of the paradigm of PAI (Pendidikan Agama Islam). According to its subject,PAI consists of three aspects; aqidah, sharia and akhlaq. It is different in certain aspects, such as: institution’slevel, the qualification of student, subject’s period and teacher’s/lecture’s understanding. This study also offersan opinion—strengthening esoteric dimensio to students, lectures and officers in order to be an integratedpersons. The formal esoteric dimension indicates esoteric weakness